People's Republic of China-Hong Kong Special Administrative Region : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
This study estimates quantitative, industry-level measures of the intensity of competition and also discusses various methodologies and data used for measuring competition. The following data are also included in the study: gross fixed capital formation, selected price indicators, labor force, employment, and unemployment, property market development, public expenditure by function, monetary indicators, balance sheet of all authorized institutions, equity price developments, exchange fund balance sheet, wages, labor productivity, public expenditure by function, revenue, government expenditure under the general revenue account, and so on.